Motivational Factors for Experienced Users of Mobile Health Applications in Heart Failure Management - Flaucher, Madeleine; Prümer, Florian; Jäger, Katharina; Rolny, Jana; Trissler, Patricia; Eckl, Sebastian; Eskofier, Björn; Leutheuser, Heike (NordiCHI '24 Adjunct: Adjunct Proceedings of the 2024 Nordic Conference on Human-Computer Interaction, 2024)
Mobile health applications have a high potential to effectively support patients with heart failure throughout their therapy by offering continuous support and personalized care. Since these applications are intended for long-term use, an important factor for their effectiveness is sustaining patient motivation. While current research has identified relevant motivational factors such as perceived usefulness and ease of use, there remains a need to deepen the understanding of what sustains long-term engagement. To address this, we conducted semi-structured interviews with patients (n = 9) and medical experts (n = 5), all of whom have extensive experience with a medically approved mobile health application. This focus on experienced users allowed us to gather detailed feedback on the app’s impact over time. From a thematic analysis, we derived the five motivational factors: Personalisation, Support, Simplicity, Overview, and Habit. Participant statements also showed that it was important for patients to have a feeling of safety, control, and usefulness while interacting with mobile health applications. The results from this study give detailed insights into relevant factors in the everyday use of patients with heart failure and provide grounds for future steps regarding the motivational design of mobile health application